The Peace Treaty of Passarowitz 1718: A Legal-Historical Analysis - Ljubović, Mirza; Silajdžić, Haris (PRAWO i WIĘŹ, 2025)
The wars fought in Europe in the late 17th and early 18th centuries were usually conflicts between European countries and the Ottoman Empire. This paper analyses the Peace Treaty of Passarowitz of 1718 using legal and historical methods. To understand how it came about, the first part of the paper provides a historical overview of the events preceding this peace agreement. A series of events and wars frequently altered the borders and territories of the warring European states over a short period. Consequently, the Peace Treaty of Passarowitz established borders and territory that endured for a longer period than those of its predecessors. The legal analysis examines the uti possidetis principle and presents it in a modern context through the lens of a historical event and document. In addition to the historical review, the paper analyses the beginnings of the negotiations, their course, the conclusion of the peace agreement and its characteristics. Having presented the peace agreement, the article will demonstrate its legal implications within the scope of modern public international law, alongside a comparative analysis of its influence on subsequent peace treaties. Lastly, it is important to recontextualise this peace treaty within the legal-philosophical evolution and demonstrate its connection to current challenges in public international law.